Liberal responses to populism - Horn, Karen 1966-; Kolev, Stefan 1981-; Müller, Julian F. 1983- (De Gruyter, 2025)
Populism has taken root almost everywhere in the West. It is crucial to understand how it has come about, where its antagonistic worldview, its nativism, its illiberalism and its anti-pluralism will take us, and how we should seek to fend off this threat to liberal democracy. In particular, what could liberal answers look like? This book is a collection of essays written by young and senior scholars in various fields from philosophy to economics. Part I explores populism's nature and causes, shedding light on the lure of sovereignty, the perceived representation gap and the process of radicalization, and human psychology. Part II is dedicated to observations inside the political arena, pitting liberalism and populism in a historical perspective, analyzing the risk of democratic backsliding, and asking how liberals should navigate the political need to make compromises. In Part III, the focus turns to liberal responses such as rules-based public deliberation, a liberal ethics attending to civic virtues, improved representation through the blockchain, and polycentric migration policies. Part IV, finally, houses critical engagements with influential relevant authors such as Foucault, Laclau, Berlin, and Harrington. Liberal Responses to Populism is a rich and thought-provoking read for scholars and students in political economy, political science, and political philosophy.